EFFECTIVENESS OF TRIPLE THERAPY WITH SINGLE AND MULTIPLE INHALERS IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Soemarwoto, Retno Ariza; Putri, Maharani; Meirissa, Tria; Yunus, Faisal; Aryana, Wayan Ferly; Wibowo, Adityo; Oktobiannobel, Jordy (Universitas Aisyah Pringsewu, 2025)
Introduction: Exacerbations of chronic obstructive pulmonary disease (COPD) contribute to 3 million annual deaths worldwide. Triple therapy (ICS + LABA + LAMA) helps reduce symptoms and exacerbation risk.Objective: To assess the effectiveness and clinical response of single versus multiple inhaler therapy in managing COPD.Methods: A pre-post study was conducted on two groups of COPD patients over 8 weeks. Group 1 (n=47) used a single inhaler, while Group 2 (n=45) used multiple inhalers. Outcomes were measured using the mMRC scale, blood eosinophil levels, and spirometry at weeks 2 and 8.Results: The single-inhaler group significantly reduced mMRC scores, with a median decrease from 4.00 to 2.00 (p0.05). Eosinophil levels also decreased significantly in both groups, with a larger reduction in the single-inhaler group (p0.05). Lung function improved in both groups, but no significant differences were found (p0.05) in terms of time or between-group comparisons.Conclusion: Single-inhaler therapy reduced dyspnea and eosinophil levels more effectively than multiple inhalers. The effectiveness of single inhalers may be attributed to higher adherence due to ease of use.